2011
DOI: 10.1002/jmor.11032
|View full text |Cite
|
Sign up to set email alerts
|

Topography and ultrastructure of the tegument of Lecithochirium musculus (digenea: Hemiuridae), a parasite of the European eel Anguilla anguilla (osteichthyes: Anguillidae)

Abstract: The tegumental ultrastructure of the stomach fluke Lecithochirium musculus was studied using scanning and transmission electron microscopy. The surface of the tegument was smooth and covered by transverse cytoplasmic ridges. Cobblestone-like units of the tegument were observed on the ventral surface. Invagination and evagination of the ecsoma induced variations in the tegumental surface. The ultrastructural study revealed that the tegument of L. musculus had a typical syncytial organization with a distal cytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…Comparison with previous studies concerning platyhelminth surface structures [3840] confirms that P. homoion share analogous morphological characteristics with other Platyhelminthes. While there have been numerous previous studies focused on the morphology and ultrastructure of monogenean surface and attachment structures using TEM [10, 11, 23, 24, 26, 27, 41], none have included species from the family Diplozoidae.…”
Section: Discussionsupporting
confidence: 84%
“…Comparison with previous studies concerning platyhelminth surface structures [3840] confirms that P. homoion share analogous morphological characteristics with other Platyhelminthes. While there have been numerous previous studies focused on the morphology and ultrastructure of monogenean surface and attachment structures using TEM [10, 11, 23, 24, 26, 27, 41], none have included species from the family Diplozoidae.…”
Section: Discussionsupporting
confidence: 84%
“…The general topography and ultrastructural organisation of the tegument in Maritrema feliui is essentially similar to that previously described for other digeneans by, inter alia, Threadgold (1963Threadgold ( , 1968Threadgold ( , 1984, Lee (1966), Burton (1966), Świderski (1966), Bogitsh (1968), Hockley (1973), Lumsden (1975), McLaren (1980), Choi and Yoo (1985), Brennan et al (1991), Cohen et al (1996), Ferrer et al (1996) and, more recently, by Filippi et al (2010Filippi et al ( , 2012Filippi et al ( , 2013. The nature of the tegumental surface of M. feliui, with infolding, pits and spines, inevitably increases the total surface area, which is probably important for the inward and outward transmission of nutrients and waste products, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…An extracellular matrix, composed of a basal matrix and an interstitial matrix, as seen in other digenean species (Filippi et al 2010(Filippi et al , 2012(Filippi et al , 2013 and in other parasitic platyhelminths (Conn 1993), occurs between the perikayra and the distal cytoplasm.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The tegument of trematodes is typically covered with spines and contains secretory vesicles and granules [18, 19], and, in A. renale , the tegument aids in the destruction of host antennal gland tubules as the host tissue is compressed and abraded [8]. Carbohydrate staining of the tegument demonstrated that it is positive for acidic sulfated mucosubstances (AB1), acidic carboxylated mucosubstances (AB2.5), and neutral sugars (PAS), likely attributable to secretory vesicles.…”
Section: Discussionmentioning
confidence: 99%